Employ information technology capabilities in building a data warehouse Organization: A case study in the national company of the domestic furniture industry - Al-Shahir, Ali Abdul Fatah (Journal of University of Human Development, 2016)
The researcher seeks in their first step of their paper to find on concept of information technology capabilities and statement types. After exhibiting the views of the writers and the researchers concerning about them. As a second step, they present their proceeding concept for information technology capabilities. The third step seeks to show the concept of a data warehouse and characteristics of the organization, and in the light of the views of writers and researchers as well, And ended committed to the concept of procedural to the data warehouse, as well as the data warehouse architecture and data modeling process it. The fourth step was to stand up to the reality of information technology capabilities in the company surveyed using the checklist as a tool to collect data and information. As well as the proposal of a model for building a data warehouse in the Home Furniture Company. The researcher reached to a number of conclusions, mainly the possibility of building a data warehouse in the company surveyed, because it will help in achieving client satisfaction through low times to provide information after they take a long time, due to the system’s ability to store data and information type and quantity and in an orderly fashion, as well as non- a redundancy in data collection and entry and processing. In light of this, the researcher presented his proposals that demonstrated the most important expand reliance on electronic systems, and address weaknesses in the IT infrastructure, as well as the need to conduct new research in other organizations to draw the attention of the departments of the importance of the data warehouse as that can contribute to the success of their organizations.